Enhancing Prudential Standards in Financial Regulations - Allen,HF; Goldstein,I; Jagtiani,J; Lang,W (Journal of Financial Services Research, 2016)
The financial crisis has generated fundamental reforms in the financial regulatory system in the U.S. and internationally. Much of this reform was in direct response to the weaknesses revealed in the precrisis system. The new “macroprudential” approach to financial regulations focuses on risks arising in financial markets broadly, as well as the potential impact on the financial system that may arise from financial distress at systemically important financial institutions. Systemic risk is the key factor in financial stability, but our current understanding of systemic risk is rather limited. While the goal of using regulation to maintain financial stability is clear, it is not obvious how to design an effective regulatory framework that achieves the financial stability objective while also promoting financial innovations. This paper discusses academic research and expert opinions on this vital subject of financial stability and regulatory reforms. Specifically, among other issues, it discusses the impact of increasing public disclosure of supervisory information, the effectiveness of bank stress testing as a tool to enhance financial stability, whether the financial crisis was caused by too big to fail (TBTF), and whether the Dodd-Frank Wall Street Reform and Consumer Protection Act (DFA) resolution regime would be effective in achieving financial stability and ending TBTF.